2023
DOI: 10.1177/11206721231167198
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes of Yamane technique in various indications

Abstract: Introduction To describe the clinical and refractive outcomes of Yamane transconjunctival sutureless intrascleral intraocular lens (SIS IOL) fixation technique in aphakic and dislocated IOLs. Methods The aphakic and IOL dispositioned patients who underwent Yamane surgery in Bozyaka Research and Training Hospital were evaluated retrospectively. The demographic data, preoperative & postoperative best-corrected visual acuity (BCVA), spherical equivalent (SE), indication for surgery, additional surgical interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…Among the 11 patients who received combined IOL fixation and other procedures, such as PPV and iris reconstruction, there were no significant intraoperative or postoperative complications reported over the long-term follow-up. Moreover, the incidence of complications was far lower than those reported in earlier studies [ 4 , 5 , 10 13 ]. The mean postoperative BCVA was significantly improved compared with that before surgery (0.39 ± 0.56 logMAR vs. 0.89 ± 0.72 logMAR, p < 0.05).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Among the 11 patients who received combined IOL fixation and other procedures, such as PPV and iris reconstruction, there were no significant intraoperative or postoperative complications reported over the long-term follow-up. Moreover, the incidence of complications was far lower than those reported in earlier studies [ 4 , 5 , 10 13 ]. The mean postoperative BCVA was significantly improved compared with that before surgery (0.39 ± 0.56 logMAR vs. 0.89 ± 0.72 logMAR, p < 0.05).…”
Section: Discussioncontrasting
confidence: 62%
“…The precise calculation of preoperative IOL power is critical, yet prior research indicates that postoperative refractive outcomes often bear a degree of unpredictability, with postoperative refractive states ranging from mild hyperopia to mild myopia. Retrospective analyses of sutureless intrascleral IOL fixation have yielded varied results; some studies report a myopic shift, while others indicate a hyperopic shift [4,5,10,[12][13][14][19][20][21]. In our study, the mean refractive difference from predicted value showed mild myopic shift (− 0.13 ± 0.42 D), aligning with the findings of Yamane et al Within our patient cohort, 63.6% exhibited a myopic shift, 36.4% a hyperopic shift, and notably, 63.6% achieved a target refractive error within 0.5 D.…”
Section: Discussionmentioning
confidence: 99%
“…1 Flanging for scleral intraocular lens (IOL) fixation salvages the advantage of being less time-consuming and highly effective and showed to have satisfiable long-term outcomes. 2 Besides the secondary fixation of IOLs, a new technique for scleral stabilization of the capsular bag and IOL centration has been proposed by Karadag et al using 2 iris hooks sutured to the scleral bed. 3 This approach yields the advantage of preserving the capsular bag during surgery in cases with zonular dialysis or subluxated crystalline lenses.…”
mentioning
confidence: 99%